2019
DOI: 10.1016/s1569-9056(19)30897-8
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin and the Rho-kinase inhibitor Y-27632 prevent myofibroblast transformation in Peyronie’s disease-derived fibroblasts via inhibition of YAP/TAZ nuclear translocation

Abstract: word count: 328 Text body word count: 3100 Abstract:Objectives: To uncover the anti-myofibroblast (MFB) properties of Rho-kinase inhibitor (compound Y-27632) and simvastatin in an in vitro model of Peyronie's disease (PD). PD is a sexual debilitating disease caused by an irreversible fibrotic plaque in the penile tunica albuginea (TA). Treatment is limited to surgically restoring anatomical shape. Evidence for effective medical treatment is lacking.Material and Methods: Primary human fibroblasts were isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Some studies have demonstrated the inhibitory effects of simvastatin and Y-27632 on TGF-β-induced myofibroblast differentiation from fibroblasts derived from different disease specimens, such as nasal polyps ( 24 ), keloids ( 20 ), and penile tunica albuginea from Peyronie’s disease ( 21 ). To the best of our knowledge, this is the first study to investigate the antifibrotic effects of simvastatin and Y-27632 in GO-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have demonstrated the inhibitory effects of simvastatin and Y-27632 on TGF-β-induced myofibroblast differentiation from fibroblasts derived from different disease specimens, such as nasal polyps ( 24 ), keloids ( 20 ), and penile tunica albuginea from Peyronie’s disease ( 21 ). To the best of our knowledge, this is the first study to investigate the antifibrotic effects of simvastatin and Y-27632 in GO-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Statins inhibit the synthesis of intermediates of cholesterol biosynthesis such as farnesyl pyrophosphate (FPP) and geranylgeranyl pyrophosphate (GGPP), which are essential for the post-translational modification of the Rho family proteins ( 8 ). Therefore, statins have a potential therapeutic role in fibrotic diseases owing to their inhibitory effects on RhoA/ROCK signaling ( 20 , 21 ). Simvastatin, a type of statin, can suppress TGF-β-induced myofibroblast transformation of fibroblasts through RhoA/ROCK inhibition ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, we acknowledged a growing interest in basic and translational research on PD pathogenesis, including the developing of the first in vitro cell culture models [10,11]. Even though, little progresses have been made towards further elucidating the real etiology of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The ROCK inhibitor, Y-27632, and simvastatin prevent fibrotic changes in TA by inhibiting YAP/TAZ nuclear translocation and downregulating CTGF mRNA expression. 124 Fasudil, a RhoA/Rho kinase (ROCK) inhibitor significantly induces the apoptosis of human fibroblasts derived from urethral scar tissues and decreases their proliferative activity in the absence or presence of TGF-β1 stimulation in a dose and time-dependent manner. Fasudil also suppresses actin polymerization and collagen synthesis, and induces apoptosis in human urethral scar fibroblasts stimulated with or without TGF-β1 via the Rho/ROCK signaling pathway.…”
Section: Introductionmentioning
confidence: 99%